Enhanced Molecular Interaction of 3D Plasmonic Nanoporous Gold Alloys by Electronic Modulation for Sensitive Molecular Detection - La, Ju A.; Lee, Hyunjoo; Kim, Dongchoul; Ko, Hyungduk; Kang, Taewook (American Chemical Society, 2024)
Three-dimensional gold and its alloyed nanoporous structures possess high surface areas and strong local electric fields, rendering them ideal substrates for plasmonic molecular detection. Despite enhancing plasmonic properties and altering molecular interactions, the effect of alloy composition on molecular detection capability has not yet been explored. Here, we report molecular interactions between nanoporous gold alloys and charged molecules by controlling the alloy composition. We demonstrate enhanced adsorption of negatively charged molecules onto the alloy surface due to positively charged gold atoms and a shifted d-band center through charge transfer between gold and other metals. Despite similar EM field intensities, nanoporous gold with silver (Au/Ag) achieves SERS enhancement factors (EF) up to 6 orders of magnitude higher than those of other alloys for negatively charged molecules. Finally, nanoporous Au/Ag detects amyloid-beta at concentrations as low as approximately 1 fM, with SERS EF up to 10 orders of magnitude higher than that of a monolayer of Au nanoparticles.